Levels of Hemoglobin, Leukocytes, and Platelets of Chronic Kidney Disease Patients Undergoing Hemodialysis in Surabaya - Mega Kahdina; Nunuk Mardiana; Dyah Fauziah (Biomolecular and Health Science Journal, 2018)
Background: Chronic kidney disease (CKD) is increasing in Indonesia, furthermore, it requires high treatment cost such as conservative therapy and kidney transplantation or dialysis. There are two types of dialysis; hemodialysis (HD) and peritoneal dialysis. The patient who undergoes HD needs periodical laboratories evaluation due to its impact on hemoglobin (Hb), leukocyte and platelets. The purpose of this study was to obtain the levels of Hb, leukocyte and platelets regularly in stage 5 CKD patients undergoing HD.Methods: Data were collected from patients’ medical record from October to December 2014 and it was characterized based on age, sex, HD frequency, HD period, hemoglobin, iron saturation, ESA (erythropoiesis-stimulating agent), leukocyte level and platelets level. 60 samples were included with the same ratio.Results: The average of age was 45 years old and the average of HD period was 40 months. All patients suffered anemia, however, only 51 patients could be evaluated the iron saturation. From it, 37 patients had the iron saturation of ≥20% which 14 (38%) of them received ESA. There were 14 patients who suffered zinc deficiency anemia with the iron saturation of <20% which 4 (29%) of them received ESA.Conclusion: Most of patients’ leukocyte and platelets levels were normal. Patients who received ESA had higher Hb levels. Platelets levels had a reverse correlation with the longer period of hemodialysis.